Expanding Nationalisms at World's Fairs Identity, Diversity, and Exchange, 1851-1915 - Raizman, David Seth 1951-2021 (Routledge Research in Art History Ser., 2017)
"Cover" -- "Half Title" -- "Title Page" -- "Copyright Page" -- "Contents" -- "List of illustrations" -- "List of contributors" -- "Introduction: communities real and imagined: worldâs fairs andÂ political meanings" -- "1 East meets West: re-presenting the Arab-Islamic worldÂ at the nineteenth-century worldâs fairs" -- "2 From London to Paris (via Cairo): the world expositions and the making of a modern architect, 1862â1867" -- "3 The Belgian reception of Italy at the 1885 Antwerp World Exhibition: converging artistic, economic, and political strategies on display" -- "4 A Danish spectacle: balancing national interests at the 1888 Nordic Exhibition of Industry, Agriculture, and Art in Copenhagen" -- "5 A neoclassical translation: the Hôôden at the 1893 Worldâs ColumbianÂ Exposition" -- "6 Paris, 1900: the Musée Centennal du Mobilier et de la Décoration and the formulation of a nineteenth-century national design identity" -- "7 âOur country has never been as popular as it is now!â: Finland at theÂ 1900 Exposition Universelle" -- "8 âA revelation of grace and prideâ: cultural memory and international aspiration in early twentieth-century Hungarian design" -- "9 When the local is the global: case studies in early twentieth-centuryÂ Chinese exposition projects" -- "10 The 1910 Centenary Exhibition in Argentina, Chile, and Uruguay: manufacturing fine art and cultural diplomacy in South America" -- "Bibliography".